Sediment-Based Unfired Bricks Reinforced with Waste Flax Fibers: Implementation, Physical Aspects and Kinetics of Air Drying—Part I - Daniel Levacher; Alexandre Suriray; Désiré Ndahirwa; Hafida Zmamou; Nathalie Leblanc; Tomoki Shimpo (Applied Sciences)
Raw earth bricks made from river sediments and natural fibers are essentially environmentally friendly bricks. They are made from river sediment waste and natural fiber waste, both of which are renewable resources. Sediment-based bricks have been formed from river sediment and flax fibers, the latter being considered as waste. Both types of waste are available in the same region. The study focused on the definition of water content by means of a miniature Proctor test, on the incorporation of short flax fibers of 2, 3 and 4 cm at various dosages and on the shaping by dynamic compaction of bricks of reduced size of 4 cm × 4 cm × 16 cm, dimensions similar to mortar specimens. The air-drying kinetics of the specimens were monitored from manufacture through to stabilization of their mass. The effects of water content, fiber content and fiber length were analyzed. Recommendations are given for the manufacturing and drying of green bricks and natural fibers.